Meningkatkan Kemampuan Menulis Recount Text Dengan Media Gambar Pada Peserta Didik Kelas X.A SMA Negeri 1 Bayan Lombok Utara - Wirebakti, Wirebakti (Lembaga Bale Literasi, 2023)
This research is about how the learning process of students is able to improve their skills in writing Recount text using picture media of tourist attractions, how much competency skills in writing Recount text can be improved using picture media of tourist attractions. What is the quality of change in social behavior, selfconfidence and responsibility in responding personally to short-term events as a form of social attitude. This research uses two cycles. The results of cycle 1 based on the results of the Recount text writing performance test showed that there were 14 students out of 24 students or 60% of students met the target of completing classical learning or above the KKM. Meanwhile, in cycle II, based on the results of the Recount text writing performance test, it was seen that there were 18 students out of 24 students or 75% of students met the target of completing classical learning or above the KKM. Thus, it can be said that the skills competency has achieved the research target.